Potensi Zeolit Sebagai Material Pembawa Agen Antimikroba dan Adsorben di Bidang kedokteran Gigi - Sunarintyas, Siti (Fakultas Kedokteran Gigi Universitas Trisakti, 2008)
Zeolites are minerals consist of crystalline solids of hydrated aluminosilicate with well defined structure containing alkali actions which can be exchanged. The structure and characteristics of zeolite make it potentially to be used in many fields as adsorbent, catalyst, ion exchanger, or molecular sieving agents. The literature review aims to study the zeolite potential as antimicrobial agent carrier and adsorbent materials in dentistry. Zeolite can be used as an antimicrobial agent carrier by exchanging its cation with metal ion which has the capability to kill microorganism. Zeolite can also be used as an adsorbent material because of its ion exchange capability and micro porous structure which may facilitate small material to adhereand be trapped. In conclusion, the structure and characteristics of zeolite make it potentially to be used in dentistry as antimicrobial agent carrier and adsorbent materials.